Molecular Responses of Human Retinal Cells to Infection with Dengue Virus - Jillian M. Carr; Liam M. Ashander; Julie K. Calvert; Yuefang Ma; Amanda Aloia; Gustavo G. Bracho; Soon-Phaik Chee; Binoy Appukuttan; Justine R. Smith (Mediators of Inflammation)
Recent clinical reports indicate that infection with dengue virus (DENV) commonly has ocular manifestations. The most serious threat to vision is dengue retinopathy, including retinal vasculopathy and macular edema. Mechanisms of retinopathy are unstudied, but observations in patients implicate retinal pigment epithelial cells and retinal endothelial cells. Human retinal cells were inoculated with DENV-2 and monitored for up to 72 hours. Epithelial and endothelial cells supported DENV replication and release, but epithelial cells alone demonstrated clear cytopathic effect, and infection was more productive in those cells. Infection induced type I interferon responses from both cells, but this was stronger in epithelial cells. Endothelial cells increased expression of adhesion molecules, with sustained overexpression of vascular adhesion molecule-1. Transcellular impedance decreased for epithelial monolayers, but not endothelial monolayers, coinciding with cytopathic effect. This reduction was accompanied by disorganization of intracellular filamentous-actin and decreased expression of junctional molecules, zonula occludens 1, and catenin-β1. Changes in endothelial expression of adhesion molecules are consistent with the retinal vasculopathy seen in patients infected with DENV; decreases in epithelial junctional protein expression, paralleling loss of integrity of the epithelium, provide a molecular basis for DENV-associated macular edema. These molecular processes present potential therapeutic targets for vision-threatening dengue retinopathy.